PHYSICAL TRAINING INDICATORS OF 11-12-YEAR-OLD BOXERS ENGAGED IN THE INITIAL PREPARATORY STAGE - S.S. Tajibayev; Nabiyev Shahboz; Qahhorjonov Abdulaziz (Journals Park Publishing, 2022)
In this article, the development levels of physical quality indicators of 11-12-year-old athletes who are engaged in training in primary training groups of children and adolescents’ sports schools are investigated.
Keywords: Physical preparation; physical qualities; strength